COVID-19 Law Lab: Building Strong Legal Evidence. Issue 2 (2022) - Aneja, Kashish; Ginsbach, Katherine; Gottschalk, Katie; Halabi, Sam; Nardi, Francesca
Abstract: The COVID-19 Law Lab platform enables quantitative representation of epidemic law and policies in a given country for multiple years, enabling governments and researchers to compare countries, and learn about the impacts and drivers of policy choices. The Law Lab initiative is designed to address the urgent need for quality legal information to support the study of how law and policy can be used to effectively manage this, and future, pandemic(s).